Exploiting Scanning Behavior for Predators Can Reduce Rice Damage Caused by Birds - Honda, Takeshi (International Journal of Zoology, 2015)
Rice is often damaged by birds, especially sparrows, in Asia. Bird nets are sometimes used as countermeasures; however this approach is expensive and labor intensive. For this reason, farmers generally eschew bird nets, even though no alternative countermeasures are available. This study focused on exploiting the bird behavior of scanning for predators to reduce crop damage. When birds forage for seeds on the ground they often stop pecking and briefly raise their heads, apparently to scan for predators. Low visibility habitats increase scanning behavior and increased scanning behavior reduces habitat quality from the bird’s perspective; therefore, this study tested the relationship between rice damage rate and visibility at the periphery of rice fields, where tree sparrows rest after feeding. Overall, low visibility reduced damage to rice. Because visibility was mainly affected by weeds, weed management techniques contribute to crop damage management. To reduce damage, weeding can be decreased; therefore, this technique is cost- and labor-efficient.